(untitled) (Research, Society and Development, 2022)
Introduction: The genus Erythrina figures as a group of bioactive-producing plants of importance to physiological and biomedical sciences, where the species Erythrina velutina is evidenced in studies by the presence of bioactive compounds with therapeutic purposes in the central nervous system (CNS). Erythrina mulungu is described as a source of compounds with antibacterial, anti-inflammatory and anti-plasmoid potential. Objectives: Evaluate and discuss the importance of the genus Erytrhrina and its action in the CNS. Method: This is an integrative review, where the research and selection of articles was carried out in the following databases: Pubmed, Scopus, Web of Science, Medline and Scielo. Results. After applying the inclusion and exclusion criteria, this study consists of the analysis and discussion of 21 articles. Studies with plant species of the genus Erythrina showed that they have multiple functions in the CNS, including: antinociceptive, sedative, antidepressant and neuroprotective properties. This suggests an indication that the characteristics of influence on the CNS are intrinsic to the genus, thus, all species of Erythrina may have some psychoactive benefit. Furthermore, studies highlight the species Erythrina mulungu, popularly consumed as a relaxant and anxiolytic related to the treatment of generalized anxiety. Conclusions: The genus of Erytrhrina has been increasingly studied regardless of its use, whether hydroalcoholic extract, essential oils, tincture or bark powder, as in in vivo studies it has become noticeable how the genus influences memory, learning, behavioral changes, anxiolytic effects, anticonvulsants and epilepsy.